Nonclassical GH Insensitivity: Characterization of Mild Abnormalities of GH Action - Storr, Helen L (Endocr Rev, 2018)
GH insensitivity (GHI) presents in childhood with growth failure and in its severe form is associated with extreme short stature and dysmorphic and metabolic abnormalities. In recent years, the clinical, biochemical, and genetic characteristics of GHI and other overlapping short stature syndromes have rapidly expanded. This can be attributed to advancing genetic techniques and a greater awareness of this group of disorders. We review this important spectrum of defects, which present with phenotypes at the milder end of the GHI continuum. We discuss their clinical, biochemical, and genetic characteristics. The objective of this review is to clarify the definition, identification, and investigation of this clinically relevant group of growth defects. We also review the therapeutic challenges of mild GHI.